Quality Evaluation of Chromatic Interpolation Algorithms for Image Acquisition System - Hernández,Diana Carolina Morón (2016)
ABSTRACT The main goal of the Libertad 2 mission is to take images of the Earth’s surface in the visible spectrum with a multispectral sensor and send them as a Bayer array. To carry out the reconstruction in land of these images and to view them in a RGB color model, it is necessary to use a color interpolation algorithm to determine the values of the different channels of color in each pixel. This document presents an analysis of five chromatic interpolation algorithms (Nearest Neighbor, Adaptive Color Plane, Bilinear, Smooth Hue Transition and Median Based). The analysis also includes the identification of image evaluation algorithms without reference and the artifacts (False Color Measure, Blur Metric and Chromatic and Achromatic Zipper). Finally, the analysis results of the chromatic interpolation algorithms and the selection of the most suitable algorithm for the Libertad 2 satellite mission data are presented.